COMMUNITY BASED TOURISM FESTIVALS IN THE MÉDIO TEJO REGION, PORTUGAL A POTENTIAL FOR THE SPECIALIZED CULTURAL CONSUMPTION OF CREATIVE TOURISM - Carvalho, Rui; Costa, Carlos; Ferreira, Ana Maria (My University, 2015)
Creative tourism is seen as an alternative to the serial reproduction of culture and the massive consumption of cultural tourism. Cultural and creative events have been highlighted as strong strategies for tourism development in creative tourism literature. Postmodern tourists seek meaningful experiences through a closer contact with local communities and act as co-creators of the overall creative tourism experience. Festivals can offer the opportunity for such phenomena in direct or indirect ways. In creative tourism both intangible and tangible cultural assets can be (re)activated for tourism purposes and creative add ups can be included in these events. Three community based tourism festivals are analyzed in reference to creative tourism literature and cultural capital theory. These events are characterized and creative strategies are suggested. By offering specialized cultural activities, this will enhance the cultural capital of participants, planners, local communities and help to differentiate tourism supply in the region. This paper aims at contributing to the research and development of creative tourism in the central region of Portugal, mainly the Médio Tejo region, which embodies thirteen municipalities in the center of the country.
Keywords: Creative tourism; Cultural capital; Creative festivals; Co-creation; Tourism experience